Profil Indeks Kesesuaian Wisata di Pantai Semawang, Kelurahan Sanur, Denpasar Berbasis Zonasi Pemanfaatan Kawasan - Ida Bagus Putu Adi Gita Saputra; I Gusti Ngurah Putra Dirgayusa; Gede Surya Indrawan (Journal of Marine Research and Technology, 2023)
The tourism suitability index (IKW) research conducted at Semawang Beach, Sanur Village, Denpasar, aimed to determine the limiting factors, the value of the tourism suitability index, and the zone of the utilization of the coastal tourism area for the recreation category. The method used is observation and survey in the field by purposive sampling at 4 station points, divided into a beach length of 710 m, and tourist interviews with as many as 50 respondents. The data include beach type, water depth, beach width, water base material, water current velocity, coastal slope, water clarity, coastal land cover, hazardous biota, and freshwater availability. The analysis of the tourism suitability index (IKW) refers to the tourism suitability matrix and the classification of the suitability of beach tourism in the recreation category. The limiting factor of the tourism suitability in Semawang Beach is the closure of coastal land. The value of the tourism suitability index (IKW) for beach tourism activities in the recreational category at Semawang Beach at the station I was 96.43%, station II was 90.48%, station III was 96.43%, and station IV was 94.04%. All stations are categorized as suitable (SS) for beach tourism activities. The used zone for coastal tourism areas for swimming, sunbathing, sports, and sightseeing can be carried out at all stations. The sacred zone is at Station II, adjacent to the entrance to the beach